2012
DOI: 10.1007/s11999-011-2056-y
|View full text |Cite
|
Sign up to set email alerts
|

Similar Outcomes for Nail versus Plate Fixation of Three-part Proximal Humeral Fractures

Abstract: Background There is a lack of consensus regarding optimal surgical management of displaced and unstable three-part proximal humeral fractures. Questions/purposes The objective of this prospective observational study was to compare the clinical and radiologic outcomes of plate versus nail fixation of threepart proximal humeral fractures. Patients and Methods Two hundred eleven patients with unstable three-part proximal humeral fractures were treated with ORIF using plate (PHILOS [proximal humeral interlocking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 30 publications
(46 reference statements)
3
78
0
10
Order By: Relevance
“…Compared to his past experience in fixing these fractures with the proximal humeral locking plate prior to the introduction of the MultiLoc nail, the main benefit seems to be the much earlier return of motion and lower complication rate. This unsubstantiated observation of ours is echoed by other authors who reported less pain in the early postoperative period 6 and a lower complication rate 7 with the use of the nail to treat displaced proximal humeral fractures.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Compared to his past experience in fixing these fractures with the proximal humeral locking plate prior to the introduction of the MultiLoc nail, the main benefit seems to be the much earlier return of motion and lower complication rate. This unsubstantiated observation of ours is echoed by other authors who reported less pain in the early postoperative period 6 and a lower complication rate 7 with the use of the nail to treat displaced proximal humeral fractures.…”
Section: Discussionsupporting
confidence: 70%
“…5 Among the many fixation methods available, proximal humeral locking nails are commonly used, with several studies showing similar outcome results compared to locked plating. 6,7 However, concerns remain regarding its complications, including rotator cuff injury. [8][9][10][11] In view of this, newer generation intramedullary nails have been introduced in a bid to improve fixation and minimize these complications.…”
Section: Introductionmentioning
confidence: 99%
“…Trepat et al 11 postulated that complications in LP group due to approach requiring more soft tissue dissection which might be avoided with a minimally invasive technique, particularly in two-part fractures, this complication could be avoided, no difference in range of motion was found with FE of 130 in the IMN group and 131 in the LP group and an average neck-shaft angle of 121 in the IMN group and 125 in the LP group after surgical fixation was reported. Konrad et al 12 compared LP and IMN in three-part fractures and functional outcome scores and results differences were statistically insignificant. The complications were secondary to surgery in which screw penetration into the joint was not recognized during surgery; hence they concluded that surgical technique is more important than implant selection.…”
Section: Discussionmentioning
confidence: 99%
“…정확한 해부학적 정복과 빠른 재활운동을 할 수 있다는 장점이 있어 관혈적 정복 및 내고정술이 근위 상완골 골절에 많이 적용되고 있으며, 최근 잠김 금속판의 . 그럼에도 불구하고, 많은 연구에서 수술적 치료 후 에 핀 또는 나사못의 이동, 고정물의 실패, 관절 내 나사못 의 돌출, 그리고 상완 골두의 골괴사 등은 여전히 드물지 않으며, 이는 좋지 않은 기능적 결과를 보고하고 있다 4,6,19) . 이에 반하여, 상완골 근위부 골절에서 가장 흔히 적용되 고 있는 보존적 치료는 비전위 골절뿐만 아니라, 전위된 2 분 골절에서도 우수한 골유합률이 보고되고 있다 5) .…”
Section: 서 론unclassified
“…평균 Constant 점수는 84.1점(범위, 53-100점)이었으며, 우수 11 예, 양호 4예, 보통 2예로 대부분에서 양호 이상의 견관절 기능을 보였다 (Table 1) . 경피적 핀고정술, 관혈적 정복 및 금속판 고정술, 골수강내 고정술과 같은 다양한 수술적 치료가 행해지고 있으나 나사못의 관절면 침투, 금 속물의 이완, 금속판의 파손과 불유합과 같은 수술 후의 합병증도 30%까지 보고되고 있다 6,9,16,19) . 이는 악화된 견관 절의 기능을 가져올 뿐 아니라 최고 40%까지의 추가적인 수술적 치료를 필요로 하므로 수술적 치료의 큰 단점이 되 며, 특히 골다공증이 동반된 경우 위의 합병증의 가능성은 높아진다 4,[13][14][15]18,19) .…”
Section: 서 론unclassified